How can we simplify sqrt(48) - 6/sqrt(3) ?

Observing that 48 = 24 * 2 = 1222 = 443, we can write square root of 48 as being square root of 443, which means that sqrt(48) = 22sqrt(3).Now, we can multiply the new result 22sqrt(3) with sqrt(3) such that we can have a common denominator on the bottom.So, 22sqrt(3)sqrt(3)/sqrt(3) - 6/sqrt(3) = (22*3 - 6)/sqrt(3) = 6/sqrt(3).If we want our answer to look prettier, we can multiply again with sqrt(3) such that the new result could look as 6 * sqrt(3) /3 = 2sqrt(3).

DG
Answered by Dorian G. Maths tutor

8428 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

The curve C has equation y=3x^3-11x+1/2. The point P has coordinates (1, 3) and lies on C . Find the equation of the tangent to C at P.


What does it mean to differentiate a function?


Prove the property: log_a(x) + log_a(y) = log_a(xy).


A matrix M has eigenvectors (3,1,0) (2,8,2) (1,1,6) with corresponding eigenvalues 1, 6, 2 respectively. Write an invertible matrix P and diagonal matrix D such that M=PD(P^-1), hence calculate M^5.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences